Development of the Nyika Plateau, Malawi: A Long Lived Paleo‐Surface or a Contemporary Feature of the East African Rift? - M. F. McMillan; S. C. Boone; B. P. Kohn; A. J. Gleadow; P. R. Chindandali (Geochemistry, Geophysics, Geosystems, 2022)
Abstract Northern Malawi's Nyika Plateau is a 3,700 km2 large, highly elevated (∼2,500 m) plateau located at the western margin of the Miocene‐Recent Malawi rift and the confluence of multiple Proterozoic orogenic belts. Neighboring asthenospheric upwelling in the Rungwe Volcanic Province, associated with the active East African Rift, has created similar topographic highs, leading some to speculate that the formation of Nyika could be related. Here, we present new low‐temperature data using apatite fission track, apatite (U‐Th‐Sm)/He and zircon (U‐Th)/He thermochronology to constrain the upper crustal thermal history of the Nyika region since the Devonian. The data suggest that Nyika was an isolated feature since at least the Permo‐Triassic, well before more recent rifting in Malawi, and may have developed as a horst between two large Karoo grabens, the Henga‐Ruhuhu and the North Rukuru to the southeast and northwest, respectively. Similarities between the thermal histories of Nyika and the currently separated Livingstone Plateau to the east allow for the possibility that these may have been connected in a contiguous highland prior to the formation of the intervening Neogene Malawi rift. Thermal history models for exposed Precambrian basement samples adjacent to Nyika, and once buried beneath the neighboring Karoo basins, indicate that up to 3.4 km of Permo‐Triassic section has since been eroded, with samples along the plateau not indicating burial of Karoo‐type sediment at this time. Most recent cooling histories suggest that the plateau surface continued to denude at varying degrees from the Cretaceous and reached near‐surface temperatures in the Late Paleogene‐Neogene.